Small-Incision Sutureless Surgical Technique for Subconjunctival Orbital Fat Prolapse. Issue 5 (July 2020) - Kim, Woojin; Yang, Sungwon; Park, Jinhwan; Lee, Hwa; Baek, Sehyun
Abstract : Abstract: Surgical outcomes of 20 patients treated by one surgeon between March 2014 and August 2019 were reviewed retrospectively. The authors included 20 patients with subconjunctival orbital fat prolapse (SOFP) treated by a small-incision, sutureless surgical technique using local anesthesia. All patients were followed for at least 3 months postoperatively. Medical information such as patient's age, number of eyes involved, location of fat, surgical time and whether or not the prolapse recurred was reviewed. Twenty patients (16 men and 4 women) were included and had a mean age of 67.1 years. There were 7 bilateral and 13 unilateral SOFP cases. There were no intra-operative or postoperative complications and no cases of recurrence within a mean follow-up of 3 months. All surgeries were successful from both cosmetic and symptomatic perspectives. Our small-incision, sutureless surgical technique is an effective method to manage SOFP. This technique, performed with local anesthesia, is both cost- and time-effective. Abstract : Supplemental Digital Content is available in the text